2000
DOI: 10.1177/009155210002800202
|View full text |Cite
|
Sign up to set email alerts
|

Community Colleges under the Microscope: An analysis of Performance Predictors for native and Transfer Students

Abstract: Stratified random samples of native and transfer students at a university were compared based on data extracted from student transcripts for 1989, 1990, and 1991. Transfers' first-semester GPAs at the university were less than their community college cumulative GPAs, but natives maintained similar upper and lower division GPAs. Regression analysis revealed, however, that upper division GPAs varied little between native and transfer students when influences of related variables were held constant. Separate regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 12 publications
3
50
1
Order By: Relevance
“…Although it is too early to identify if early access to this capital, during the traditional period of "transfer shock" will relate to persistence in their STEM degree program, other studies have identified the importance of such transfer supports for persistence. 11 Even though Transfer students were utilizing fewer academic supports and enrichments than Transfer-GEMS students, the high percentage of these students who wanted to utilize these resources suggests that these types of supports would meet a critical need for transfer students. Thus it would appear that Transfer-GEMS may be providing students better access to or awareness of desired resources that Transfer students have not managed to discover on their own, despite the current availability of these resources on campus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it is too early to identify if early access to this capital, during the traditional period of "transfer shock" will relate to persistence in their STEM degree program, other studies have identified the importance of such transfer supports for persistence. 11 Even though Transfer students were utilizing fewer academic supports and enrichments than Transfer-GEMS students, the high percentage of these students who wanted to utilize these resources suggests that these types of supports would meet a critical need for transfer students. Thus it would appear that Transfer-GEMS may be providing students better access to or awareness of desired resources that Transfer students have not managed to discover on their own, despite the current availability of these resources on campus.…”
Section: Discussionmentioning
confidence: 99%
“…Our initial findings suggest curricular programs providing early access to academic enrichments and supports for STEM transfer students may be critically important to ease "transfer shock" of these students by providing capital. 11 Universities would be wise to invest time and resources to ensure their websites provide information specifically for transfer students, such as degree progression plans and course transfer guides, to not only attract transfer students to their STEM programs but, should these efforts increase applications and admissions, this may also increase the diversity of their student population 5 with students who are potentially more likely to complete degree programs 11 than first-time freshmen. Additionally, institutions should consider offering transfer students orientation in much the same depth that it does for first-time freshman as transfer students are similarly unfamiliar with the campus, course management and enrollment systems, academic services, common school acronyms, student clubs, welcome week activities, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This lack of attention and support only deepens the divide between the educational quality of two-and fouryear schools (Sandy et aI., 2005). Students educated within this system continue to fall behind their four-year counterparts (Carlan & Byxbe, 2000), begging the question of whether the community college provides a "gradual transition to the rigors of college life" (Hills, 1965, p. 201) The definition for the current study is simplified by the fact that only students who have successfully transferred to the four-year institution will be analyzed. However, the paths students take through the community college to eventually transfer are varied (Bradburn & Hurst, 2001;Cohen & Brawer, 2008).…”
Section: General Populationmentioning
confidence: 99%
“…Professors have also been accused of coddling students, with some reports showing that faculty were as much as a letter grade more lenient in some subjects than faculty at fouryear institutions (Carlan & Byxbe, 2000). This potential grade inflation, coupled with the student population and less rigorous demands, can be a hindrance to adequate learning and can affect transfer students later in their career at the senior institution (Laanan, 1996).…”
Section: Does the Community College Help Or Hinder Student Success?mentioning
confidence: 99%